2021
DOI: 10.1101/2021.10.19.465070
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Single-Cell Approach Reveals Variation in Cellular Phage-Producing Capacities

Abstract: Virus burst size, a component of viral fitness, is the average number of viral particles released from a single infected cell. In this study, we estimated bacteriophage lambda (λ) burst size mean and distribution at different lysis times. To estimate phage λ burst sizes at single-cell level, we employed a lysis-deficient E. coli lysogen, which allowed chemical lysis at desired times after the induction of lytic cycle. Induced cultures of E. coli lysogen were diluted and aliquoted into the wells of 96-well plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…However, the deletion did not greatly delay lysis because holin-mediated membrane permeabilization reduced protein synthesis, ceasing phage production, and thus eliminating the trade-off that is an important assumption of optimality models. In contrast, our holin mutants with significantly longer lysis times show continued phage production ( 40 ). Our experimental set up was sensitive to dilution due to a constant flow rate, and the strains with lysis times that deviate from the optimum range show reduced phage productivity over subsequent transfers ( Fig.…”
Section: Resultsmentioning
confidence: 87%
“…However, the deletion did not greatly delay lysis because holin-mediated membrane permeabilization reduced protein synthesis, ceasing phage production, and thus eliminating the trade-off that is an important assumption of optimality models. In contrast, our holin mutants with significantly longer lysis times show continued phage production ( 40 ). Our experimental set up was sensitive to dilution due to a constant flow rate, and the strains with lysis times that deviate from the optimum range show reduced phage productivity over subsequent transfers ( Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Some studies have indicated that burst size can be influenced by the ratio of host cell volume to virus volume ( 71 ). In the case of phages, Choi et al ( 72 ) observed that the burst size of T4 phage is greater in larger host cells, while Kannoly et al ( 73 ) found a positive correlation between burst size and cell volume in lambda phage. In fact, the likelihood of lysogeny in lambda phage increases in small cells during both the stationary and exponential phases ( 74 ), possibly due to the larger viral progeny produced in larger cells.…”
Section: Discussionmentioning
confidence: 99%
“…The latent period determines the time that a phage spends on linear reproduction within a cell, i.e. the burst size ( Kannoly et al. 2021 ), as opposed to the potential geometric increase attained by infecting new cells.…”
Section: Phenotypic Flux Through Physiological Variationmentioning
confidence: 99%
“…In this case, very short latent periods would be disadvantageous as they would lead to few or even no phage progeny released, which could explain the low variance observed in empirical measurements of latent period distributions ( Cahill and Young 2019 ). Except for very short latent periods, however, the variation in burst size is potentially only weakly influenced by variation in latent period ( Kannoly et al. 2021 ).…”
Section: Phenotypic Flux Through Physiological Variationmentioning
confidence: 99%